2009
DOI: 10.1021/jm801270e
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Drug Design of Novel Aurora Kinase A Inhibitors: Structural Basis for Potency and Specificity

Abstract: Aurora kinases have emerged as attractive targets for the design of anticancer drugs. Through structure-based virtual screening, novel pyrazole hit 8a was identified as Aurora kinase A inhibitor (IC(50) = 15.1 microM). X-ray cocrystal structure of 8a in complex with Aurora A protein revealed the C-4 position ethyl carboxylate side chain as a possible modification site for improving the potency. On the basis of this insight, bioisosteric replacement of the ester with amide linkage and changing the ethyl substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…An attractive alternative to inhibitors blocking the active site of Plk kinases is the development of compounds interfering with the binding abilities of the more diverse PBD domains, potentially yielding more selective inhibitors of Plk1 (27). Many other compounds with activities directed against Plk and Aurora kinases are now beginning to emerge (28)(29)(30)(31). Extensive research is clearly needed to validate specificities and relative efficiencies of all novel compounds.…”
Section: Plk1 and Aurora-a In Cancermentioning
confidence: 99%
“…An attractive alternative to inhibitors blocking the active site of Plk kinases is the development of compounds interfering with the binding abilities of the more diverse PBD domains, potentially yielding more selective inhibitors of Plk1 (27). Many other compounds with activities directed against Plk and Aurora kinases are now beginning to emerge (28)(29)(30)(31). Extensive research is clearly needed to validate specificities and relative efficiencies of all novel compounds.…”
Section: Plk1 and Aurora-a In Cancermentioning
confidence: 99%
“…Moreover, we have also recently reported a series of pyrazole Aurora kinase inhibitors bearing hydrazone side chain [25]. In several of these inhibitors, X-ray crystallography showed that the pyrazole ring is involved in the essential hydrogen bond interaction with the hinge region amino acid residues of Aurora kinase enzyme.…”
Section: Library Preparationmentioning
confidence: 99%
“…Analysis of these set of compounds revealed that some had a hydrazone functional group embedded in them. We have already reported several compounds bearing hydrazone fragments as Aurora kinase inhibitors, including those with pyrazole rings [14,25]. The pyrazole-hydrazones reported in ref 25 could not be further developed due to their chemical instability.…”
Section: Library Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The goals of such methods include identifying effective modifications of existing lead compounds, as well as discovering novel lead compounds (de novo design). In recent years, several cases of successful applications of structure-based drug design have been reported (Combs 2007;Coumar et al 2009;Khan et al 2010;van Montfort and Workman 2009). Given the threedimensional structure of a target molecule, chemical compounds having potentially high affinity for this target can be designed rationally with the aid of computational methods.…”
Section: Structure-based Approachesmentioning
confidence: 99%